Effect of various leachate recirculation strategies on batch anaerobic digestion of solid substrates. (1st January 2012) - Kusch, Sigrid; Oechsner, Hans; Jungbluth, Thomas
Various leachate recirculation strategies were applied to a batch-wise operated solid-phase digestion system in laboratory-scale tests. Comparative experiments with both continuous and intermittent leachate recirculation revealed no advantages of a continuous flow. Results suggest that leachate recirculation should not be carried out continuously during process initialisation when methanogenesis is the rate-limiting step. Continuous watering resulted in the accumulation of Volatile Fatty Acids (VFA) during process start-up. In addition, no need for continuous water circulation was found for the following digestion process when hydrolysis was rate-limiting. Even in the absence of liquid recirculation, degradation was only slightly retarded when the biomass moisture content was adjusted.